The noise exposure at a municipal mechanical-biological waste treatment plant - Gronba-Chyła, Anna (Instal, 2022)
Poland in the European Union statistics, takes the penultimate place, in terms of generated municipal waste in Europe an countries. By 2035, in accordance with the EU law, Member States are to achieve a recycling level of 65% for municipal waste. According to GUS data for 2020, Poland reached a general recycling level of 26.7%, excluding bio-degradable waste. Pressure from the European Union, for much higher recycling levels, is prompting the construc tion of many more modern facilities, including mechanical-biological treatment (MBT) plants. MBT plants often have difficult working conditions for employees: A very foul odor, excessive light, biological hazards, rodents and noise. Excessive noise, can not only damage hearing, but can also cause other negative health issues. Examples, include reduced mental capacity, reduced precision of movement and visual disturbances. The purpose of the research presented here, was to analyze and study noise exposure in selected areas of the MBP plant in order to determine the maximum and average exposure of workers to this factor.
Keywords: MBT; noise exposure; municipal waste